National and state-level politics on social media: Twitter, Australian political discussions, and the online commentariat - Highfield, Tim (2013)
This paper examines the use of Twitter for long-term discussions around Australian politics, at national and state levels, tracking two hashtags during 2012: #auspol, denoting national political topics, and #wapol, which provides a case study of state politics (representing Western Australia). The long-term data collection provides the opportunity to analyse how the Twitter audience responds to Australian politics: which themes attract the most attention and which accounts act as focal points for these discussions. The paper highlights differences in the coverage of state and national politics. For #auspol, a small number of accounts are responsible for the majority of tweets, with politicians invoked but not directly contributing to the discussion. In contrast, #wapol stimulates a much lower level of tweeting. This example also demonstrates that, in addition to citizen accounts, traditional participants within political debate, such as politicians and journalists, are among the active contributors to state-oriented discussions on Twitter. Copyright © 2013 Inderscience Enterprises Ltd.